2014
DOI: 10.3389/fmicb.2014.00399
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of anaerobic ammonia-oxidizing (anammox) bacteria

Abstract: Anaerobic ammonia-oxidizing (anammox) bacteria are able to oxidize ammonia and reduce nitrite to produce N2 gas. After being discovered in a wastewater treatment plant (WWTP), anammox bacteria were subsequently characterized in natural environments, including marine, estuary, freshwater, and terrestrial habitats. Although anammox bacteria play an important role in removing fixed N from both engineered and natural ecosystems, broad scale anammox bacterial distributions have not yet been summarized. The objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(108 citation statements)
references
References 104 publications
(186 reference statements)
5
99
0
4
Order By: Relevance
“…The microbial process is regulated by various environmental factors, and many studies have reported the controlling factors of anammox bacterial abundance and activity, primarily including the temperature (Schubert et al 2006;Hou et al 2013;Zhao et al 2013;Canion et al 2014), water column NO 3 − /NO 2 − availability (Meyer et al 2005;Rich et al 2008;Nicholls and Trimmer 2009;Hou et al 2013), sediment organic carbon concentration (Dalsgaard and Thamdrup 2002;Trimmer et al 2003;Hu et al 2012a) and salinity (Dale et al 2009;Hou et al 2013;Sonthiphand et al 2014). In the current study, Pearson moment correlation analyses showed that both the activity and abundance of anammox bacteria significantly correlated with the soil ammonium concentration in the examined soil cores (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The microbial process is regulated by various environmental factors, and many studies have reported the controlling factors of anammox bacterial abundance and activity, primarily including the temperature (Schubert et al 2006;Hou et al 2013;Zhao et al 2013;Canion et al 2014), water column NO 3 − /NO 2 − availability (Meyer et al 2005;Rich et al 2008;Nicholls and Trimmer 2009;Hou et al 2013), sediment organic carbon concentration (Dalsgaard and Thamdrup 2002;Trimmer et al 2003;Hu et al 2012a) and salinity (Dale et al 2009;Hou et al 2013;Sonthiphand et al 2014). In the current study, Pearson moment correlation analyses showed that both the activity and abundance of anammox bacteria significantly correlated with the soil ammonium concentration in the examined soil cores (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…To date, 16 species of anammox bacteria associated with five known candidate genera (Brocadia, Kuenenia, Anammoxoglobus, Jettenia, and Scalindua) have been described (27). The research on anammox is mostly focused on its role in the oceanic N cycle, and more than 50% of N 2 loss in some marine environments was found to be contributed by anammox (28,29).…”
mentioning
confidence: 99%
“…Various functional genes have been used as anammox biomarkers in marine systems (Table S7 in the Supplement): Scalindua-like nirS, which codes for a NirS specific to Scalindua, the dominant anammox bacteria in marine OMZs (Lam et al, 2009;Li et al, 2013); hzoAB (Hirsch et al, 2011;Lisa et al, 2014), which codes for part of the HZO, and with numerous divergent copies in a number of anammox bacteria − and NO 2 − typically favors denitrifying microorganisms over anammox bacteria (Risgaard-Petersen et al, 2005). In addition, in many marine environments anammox activity and bacterial distribution are highly dependent upon organic C content (Shehzad et al, 2016;Trimmer et al, 2003), salinity (Hou et al, 2013;Rich et al, 2008;Shehzad et al, 2016;Sonthiphand et al, 2014) and temperature Shehzad et al, 2016). For example, in eutrophic environments, high organic C concentrations usually stimulate denitrification while suppressing anammox because of the 25 competition for NO 2 − (Brin et al, 2014;Jäntti et al, 2011;Nicholls and Trimmer, 2009).…”
Section: Anammoxmentioning
confidence: 99%